An intelligent travel book management system. (24th September 2009) - Chang, Han-Bin; Chang, Hsuan-Pu; Hsu, Hui-Huang; Chao, Louis R., Timothy K. Shih
Travelling is a common activity for pleasures nowadays. With the development of transportation, visitors can easily make tours anywhere. They often use various digital devices such as video cameras to capture images during journeys. Due to the convenience of internet, more and more users make travel notes and share experience to other users via web pages. In this paper, an intelligent travel book management system is proposed to help users to easily handle multimedia information captured in a journey and repackage them for further usage. Internet technologies like agent and mobile computing are used for implementing such framework.